2023
DOI: 10.1186/s12967-023-04032-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of ACADVL is involved in the high-intensity interval training-associated reduction of cardiac fibrosis in heart failure patients

Abstract: Background Emerging evidence suggests that DNA methylation can be affected by physical activities and is associated with cardiac fibrosis. This translational research examined the implications of DNA methylation associated with the high-intensity interval training (HIIT) effects on cardiac fibrosis in patients with heart failure (HF). Methods Twelve HF patients were included and received cardiovascular magnetic resonance imaging with late gadoliniu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Our work has shown that HIIT provided a robust stimulus of ≈15% to 21% increase of O 2peak in patients with the 3 different HF phenotypes, which was similar to findings found in several previous studies. 4 , 7 , 8 Aerobic capacity was not followed for patients with HF who underwent GDMT because clinicians did not refer them for secondary CPET examination in the study. However, the decrease of O 2peak in GDMT participants could be expected, because a significant decrease of O 2peak has been reported in patients with HFrEF without HIIT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our work has shown that HIIT provided a robust stimulus of ≈15% to 21% increase of O 2peak in patients with the 3 different HF phenotypes, which was similar to findings found in several previous studies. 4 , 7 , 8 Aerobic capacity was not followed for patients with HF who underwent GDMT because clinicians did not refer them for secondary CPET examination in the study. However, the decrease of O 2peak in GDMT participants could be expected, because a significant decrease of O 2peak has been reported in patients with HFrEF without HIIT.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline demographic information and differences in LV geometric changes between the HIIT and GDMT participants with different HF phenotypes were compared using Student t test for continuous variables, and χ 2 test was conducted to assess categorical variables. In addition, clinical information assessed in the study, including cardiorespiratory fitness, LV geometry, and questionnaire for quality of life, were considered as possible confounders according to our serial works 4 , 5 , 6 , 7 , 8 , 15 and other prior publications 16 , 17 for related HF studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased methylation of RASAL1 promoter diminished RASAL1 expression and ultimately led to cardiac fibrosis [62]. Cardiopulmonary exercise in heart failure patients was reported to reduce cardiac fibrosis via hypermethylation of acyl-CoA dehydrogenase very long-chain (ACADVL) gene [63]. Furthermore, studies have shown that the promoter region of the genes encoding matrix metalloproteinases (MMPs), which are enzymes involved in ECM degradation, are targeted by DNA methylation.…”
Section: Dna Methylationmentioning
confidence: 99%